Social and Religion Paralysis in James Joyce’s Short Story The Sisters: A Cultural Reading - Safoura Eskandari (Budapest International Research and Critics University, 2020)
AbstractThis paper attempts to demonstrate how James Joyce`s short story The sisters reflects notion of social and religion paralysis functions within the framework of cultural materialism at the beginning of the Twentieth century in Irish society. Religion is major concern of cultural studies. Religion as a cultural politics is a dominant factor in shaping mind as well in affecting the framework of literary text. Religion is one of the emerging issues in the modern era and forms the backbone of most literary works. Religion as a theme is seen to influence the operation of those who believe in it. It forms the functional framework that predetermines ones actions and behavior. Williams argues that each kind of activity in fact suffers, if it is wholly abstracted and separated. Politics, for example, has gravely suffered by its separation from ordinary relationships, and we have seen the same process in economics, science, religion and education. Williams defines Residual as some social or cultural practice which has been formed in the past, but it is still active and effective in the present cultural system like organized religion. A residual cultural element is usually at some distance from the effective dominant culture, but it is some part of it which is embedded in cultural system. The concept of emergent for Raymond Williams means the creation of new meaning and values, new cultural practices and new relationships within the dominant structure. It is important to distinguish between those emergent which are elements of new stage of the dominant culture and those which are actually other element or oppositional to dominant system. This study aims to argue that paralysis is a problem and a solution and that sometimes what appears to be an escape from paralysis merely reinforces its negative manifestation. Paralysis cannot be avoided. Rather, it is something that should be engaged and used to redefine individual and social states.